“The Ecological Person” in the Digital Era - D. Z. Akhmetova (Высшее образование в России)
The author of the article raises a topical question: “How will digitalization turn the humanity – towards civilization or collapse?” With a reliance on the “The Human quality” by Aurelio Peccei, a new project was justified aimed at preserving a person and educating a healthy personality. The project implementation requires at least 16–18 years. The successive system for the development of an “ecological person” focuses on the prevention of hereditary impairement and consists of six stages and is reinforced by already existing experience of several centers and institutions where innovative approaches to the development of a healthy personality are tested, starting from the embryonic period until adulthood.